Detailed physical map of human chromosomal region 11q12-13 shows high meiotic recombination rate around the MEN1 locus. - Janson, M (1991)
We have constructed a physical map of the region q12-13 on chromosome 11 by combining data generated from a panel of radiation-reduced somatic cell hybrids and pulsed-field gel electrophoresis (PFGE). Twenty different genetic markers have been sublocalized and ordered within this region and a total of 8.0 megabases has been mapped in detail using rare-cutting restriction endonucleases and PFGE. In two instances, the long-range restriction PFGE map spans the total distance between pairs of loci that have been previously mapped by genetic linkage in reference families. Comparison of this physical map with the available linkage map indicates a great variation in the recombination frequency over the region. The recombination rate is higher than expected, particularly for markers flanking the MEN1 region. Thus, for the closest pair of linked markers on the centromeric side, one centimorgan corresponds to approximately 300 kilobases, and for markers on the telomeric side, one centimorgan corresponds to approximately 350-600 kilobases.